2013
DOI: 10.1152/ajpcell.00228.2012
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16F is a component of a Ca2+-activated Cl channel but not a volume-sensitive outwardly rectifying Cl channel

Abstract: TMEM16 (transmembrane protein 16) proteins, which possess eight putative transmembrane domains with intracellular NH2- and COOH-terminal tails, are thought to comprise a Cl− channel family. The function of TMEM16F, a member of the TMEM16 family, has been greatly controversial. In the present study, we performed whole cell patch-clamp recordings to investigate the function of human TMEM16F. In TMEM16F-transfected HEK293T cells but not TMEM16K- and mock-transfected cells, activation of membrane currents with str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
158
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(176 citation statements)
references
References 38 publications
15
158
3
Order By: Relevance
“…This is consistent with prior reports of its secretory activity in animal models (5,17,39). Using human epithelial colorectal adenocarcinoma cells, Caco-2 which possessed the machinery for Cl Ϫ transport, we showed that Ace acutely stimulated Cl Ϫ secretion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with prior reports of its secretory activity in animal models (5,17,39). Using human epithelial colorectal adenocarcinoma cells, Caco-2 which possessed the machinery for Cl Ϫ transport, we showed that Ace acutely stimulated Cl Ϫ secretion.…”
Section: Discussionsupporting
confidence: 93%
“…Each member is predicted to have multiple isoforms being simultaneously expressed in a given cell (15). Apart from ANO1 and ANO2, ANO6 was also recently shown to be a Ca 2ϩ -activated Cl Ϫ channel with delayed Ca 2ϩ activation (16,17). Despite numerous reports on ANO as a Cl Ϫ channel, the contribution of specific member(s) of this protein family to Cl Ϫ secretion in diarrhea remains obscure.…”
mentioning
confidence: 99%
“…These results came as a surprise, since Ano6 has been characterized as a Ca 2þ -activated Cl 2 channel. Moreover, Ca 2þ -activated Cl 2 currents were also observed after overexpression of Ano4, 7 and 9 [6,55,56,61,62]. However, Cl 2 channel and scramblase activity were shown to be independent [55].…”
Section: Other Anoctamins Correlated To Cancermentioning
confidence: 95%
“…It was also shown to be activated during cell swelling, probably secondary to an increase in intracellular Ca 2þ [5]. While some detected a role of Ca 2þ -dependent anoctamins, such as Ano1 or Ano6, to volume regulation, others did not [5,6]. Upregulation of endogenous Ca 2þ -activated Cl 2 channels in proliferating cells has been observed recently, but the role of these channels for proliferation has remained unclear [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Okada and coworkers found that ANO6 K D has no effect on staurosporine induced AVD. 154 Hence, the role of ANO6 in AVD/apoptosis seems to vary among cell types.…”
Section: Apoptosismentioning
confidence: 99%